Design limitations of using magnetic inductive coupling to verify nasogastric tube placement - O'Loughlin, Declan (My University, 2023)
Nasogastric tube insertion is a standard procedure but with potentially fatal consequences if misplaced. Many bedside methods have been proposed for identifying misplace- ment including magnetic inductive coupling. This study aims to identify the coil design limitations for nasogastric tube placement confirmation using magnetic inductive coupling. The fundamental limits on the coil sizes and detection distances are identified based on the anatomical understanding. Candidate designs are simulated and fabricated, and key parameters such as coil radius and penetration depth are examined. Specifically, the mutual inductance and coupling factor between the coils in the candidate designs are both calculated and measured with respected to distance. This work highlights that a small coil of up to 3 mm in diameter could be integrated into a nasogastric tube without impairing clinical function. These preliminary results suggest that magnetic inductive coupling is a promising approach for nasogastric tube localisation, however, optimisation of the detector coil size could improve localisation performance.
17th European Conference on Antennas and Propagation
PUBLISHED
Florence, Italy
Keywords: electromagnetic coupling; electromagnetic induction; inductive power transmission; medical devices and systems; mutual coupling; Next Generation Medical Devices